A clinical study comparing polymer and gold fiducials for prostate cancer radiotherapy - Lim Joon, Daryl; Berry, Colleen; Harris, Benjamin; Tacey, Mark; Smith, Drew; Lawrentschuk, Nathan; Schneider, Michal Elisabeth; Fraser, Olivia; Hall, Megan; Chao, Michael; Foroudi, Farshad; Jenkins, Trish; et al. (Frontiers in Oncology, 2023)
Introduction Image guidance with gold fiducials improves outcomes of prostate radiotherapy. However, gold produces artefact on CT imaging, interfering with contouring and verification. The purpose of this study was to compare polymer to standard gold fiducials using radiotherapy imaging modalities to assess the visibility and artefact. Methods Twenty eight patients with locally advanced prostate cancer were enrolled, half had three polymer fiducials implanted into the prostate and half underwent insertion of gold fiducials. Patients were imaged with CT, T2 weighted MRI, cone-beam CT (CBCT) and planar KV images. Fiducials were scored for visibility and assessed for CT artefact in surrounding prostate tissue. The artefact was quantified from Hounsfield number histograms and separated into percentile ranges and proportion of voxels in HU normal tissue range of a 2cm sphere surrounding the fiducial. Results Gold and polymer fiducials were sufficiently visible for CT and CBCT verification. The gold fiducials could be visualized well on KV planar imaging; however, the polymer markers were obscured by pelvic bones. Neither polymer nor gold fiducials could be visualized on MRI. The polymer fiducial produced less artefact than gold on CT, having less voxel spread for the HU percentile ranges and a greater proportion of voxels in the normal tissue range. Conclusions Polymer fiducials are a more suitable fiducial than gold for CT/CBCT in prostate cancer radiotherapy, demonstrating minimal artefact and good visibility on CT. However, they were not well seen on MRI or KV imaging and thus not suitable for co-registration or planar KV verification.